1998
DOI: 10.1002/(sici)1099-1646(199807/08)14:4<329::aid-rrr505>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

A spatial assessment of hydrologic alteration within a river network

Abstract: Maintaining natural hydrologic variability is essential in conserving native riverine biota and river ecosystem integrity. Hydrologic variation plays a major role in structuring the biotic diversity within river ecosystems as it controls key habitat conditions within the river channel, the floodplain, and hyporheic (stream‐influenced ground water) zones. Alterations in streamflow regimes may modify many of these habitat attributes and impair ecosystem connectivity. We demonstrate use of the ‘Range of Variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
313
1
11

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 505 publications
(362 citation statements)
references
References 12 publications
7
313
1
11
Order By: Relevance
“…The results of this linear regression are comparable to those reported by Clausen and Biggs (1997) for rivers in New Zealand, where a single flow variable (FRE3 -frequency of high flow events greater than three times the median discharge) accounted for between 41% and 52% of the variance in periphyton communities (25 sites), and between 14% and 36% of the variance in the macroinvertebrate communities (62 sites). In marked contrast to previous studies, the results of this study indicate that the flow magnitude ('Group 1 -magnitude of monthly water conditions' and 'Group 2 -magnitude and duration of annual extreme water conditions' of the Indicators of Hydrologic Alteration: Richter, et al, 1996Richter, et al, , 1998 were the 'best' predictors of macroinvertebrate community response to flow. The predominance of these variables within hydroecological models may reflect the variable temperate maritime climate of England and Wales and the absence of intermittent and snowmelt dominated riverine systems within the dataset reported in other investigations (Poff, 1996;Clausen and Biggs, 1997;Poff, et al, 1997;Clausen and Biggs, 2000;Olden and Poff, 2003).…”
Section: Regression Modelscontrasting
confidence: 99%
See 3 more Smart Citations
“…The results of this linear regression are comparable to those reported by Clausen and Biggs (1997) for rivers in New Zealand, where a single flow variable (FRE3 -frequency of high flow events greater than three times the median discharge) accounted for between 41% and 52% of the variance in periphyton communities (25 sites), and between 14% and 36% of the variance in the macroinvertebrate communities (62 sites). In marked contrast to previous studies, the results of this study indicate that the flow magnitude ('Group 1 -magnitude of monthly water conditions' and 'Group 2 -magnitude and duration of annual extreme water conditions' of the Indicators of Hydrologic Alteration: Richter, et al, 1996Richter, et al, , 1998 were the 'best' predictors of macroinvertebrate community response to flow. The predominance of these variables within hydroecological models may reflect the variable temperate maritime climate of England and Wales and the absence of intermittent and snowmelt dominated riverine systems within the dataset reported in other investigations (Poff, 1996;Clausen and Biggs, 1997;Poff, et al, 1997;Clausen and Biggs, 2000;Olden and Poff, 2003).…”
Section: Regression Modelscontrasting
confidence: 99%
“…The 'ecologically-relevant' hydrological variables were identified from previous research reported within 15 hydrological and ecological journal papers (see Appendix I, Hughes and James, 1989;Poff and Ward, 1989;Richards, 1989;Biggs, 1990;Jowett and Duncan, 1990;Poff, 1996;Richter, et al, 1996;Clausen and Biggs, 1997;Puckridge, et al, 1998;Richter, et al, 1998;Clausen and Biggs, 2000;Clausen, et al, 2000;Wood, et al, 2000;Wood, et al, 2001). Flow variables were assigned to one of five hydrological regime facets, as originally proposed in the Indicators of Hydrologic Alteration methodology (Richter, et al, 1996) and its derivatives (Poff, et al, 1997;Olden and Poff, 2003).…”
Section: Correlation and Regression Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Among the hydrology parameters, annual multiday minimum flows and monthly mean flows in the dry season altered moderately or highly, indicating that the low-flow regime was easily influenced by the flow diversion (Shiau . Baojiaxia diversion project had significant impacts on hydrology regime, but these effects generally attenuate with distance downstream toward Tongguan except for X-L reach, which was in accordance with the results from Richter et al (1998). Urbanization had a number of important effects on hydrology (Bobbi et al 2013).…”
Section: Hydrology Regimesupporting
confidence: 83%